1999
DOI: 10.1016/s0304-3959(99)00036-6
|View full text |Cite
|
Sign up to set email alerts
|

What are the qualities of dilemmas experienced when prescribing opioids in general practice?

Abstract: The decision process preceding prescribing analgesics is complex and the physician is often struggling to balance several disparate considerations in order to work out what is rational. Several factors--medical, intellectual, emotional and logistic--influence the decision whether or not to prescribe, and the decision itself influences how the physicians feel about themselves. In this study the 'critical incident technique' was used for exploring the qualities of dilemmas among general physicians prior to presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 17 publications
2
49
0
Order By: Relevance
“…Most providers we interviewed experienced difficulty coping with the ambiguity of making decisions about chronic opioid pain management. Our findings support those of Bendtsen et al, who reported that the quandary of prescribing opioids led to dissatisfaction with decisions, low self-esteem, and discontent with colleagues 9 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Most providers we interviewed experienced difficulty coping with the ambiguity of making decisions about chronic opioid pain management. Our findings support those of Bendtsen et al, who reported that the quandary of prescribing opioids led to dissatisfaction with decisions, low self-esteem, and discontent with colleagues 9 .…”
Section: Discussionsupporting
confidence: 91%
“…To successfully manage chronic pain with opioids, providers must balance analgesia and restoration of function with the risks of diversion, dependence, and addiction. Variability in opioid prescribing practices may be explained in part by the inherent uncertainty of the opioid risk-benefit equation [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in many states, a disability diagnosis constitutes a key criterion for eligibility for the program (32). The substantial amount of documentation required to establish this diagnosis may also attenuate any providers' concerns that their patients' complaints of chronic pain may be spurious (33). Second, to the extent that the time physicians are able to spend with Medicaid patients is constrained, they may lack the time to consult their state's prescription monitoring program concerning their patients' history of prescriptions for controlled substances.…”
Section: Limitationsmentioning
confidence: 99%
“…cal dependence, tolerance and addiction [21][22][23][24][25] ; concern about possible diversion of opioid medication for other purposes 12,15,23,24,[26][27][28][29] ; and concern about possible sanctions by state and federal regulatory agencies. 21,27,28,[30][31][32][33] These concerns may complicate clinical decision making regarding the prescription of opioids 34,35 and may result in extra time demands, failures in the patient-physician relationship, and less time on other activities.…”
Section: O Pioid T Her a P Y A Nd Pr E V En T Iv E Serv Ic Esmentioning
confidence: 99%